Two-year follow-up of posterior corneal elevation after small incision lenticule extraction for moderate myopia - Shaimaa M. Azzam; Reham R. Shabana; Hazem A. Elbedewy (Journal of the Egyptian Ophthalmological Society)
Purpose To assess the changes in the posterior corneal elevation two years after small incision lenticule extraction (SMILE) in patients with moderate myopia. Methods Total 35 patients (70 eyes) who underwent SMILE operation were included in this study. Posterior corneal elevation (PCE), the average posterior central elevation change (ΔPCE) were assessed by Pentacam images at 6 months and 2 years after surgery (January 2022–December 2023). Uncorrected and best corrected distance visual acuities (UCDVA and BCDVA), and manifest refraction spherical equivalent (MRSE) were evaluated. These data were compared to the preoperative ones. Results The safety and efficacy indices were 1.00±0.03 and 0.95±0.08, respectively. All the eyes were within ±1.00 D 2 years after surgery. In the sixth postoperative month, the mean PCE was 2.61±2.88 and the mean ΔPCE was 0.68±3.45. After 2 years of surgery, the mean PCE was 1.98±2.72, and the mean ΔPCE was 0.02±1.17. Thirty-five (50%) eyes showed +ve ΔPCE (foreword posterior corneal surface protrusion) at 6 months of surgery, 30 (85.7%) of them showed decreased positivity (posterior surface moved posteriorly), while five (14.3%) eyes of them remained stable 2 years after surgery. Conclusion SMILE procedure resulted in changes in the PCE. However, these changes remained stable and within the normal range for 2 years after surgery. SMILE can be considered as a safe procedure for moderate myopia for 2 years of observation.